Utilizing dynamic load balancing to improve private cloud paradigm - Sharmah, Daisy; Bora, Kanak Chandra; Noorain, Md; Karmacharya, Yogita (International journal of information technology (Singapore. Online), 2024)
In today's changing world businesses are increasingly relying on private cloud solutions to meet their specific needs, for growth and effectiveness. This research paper explores the realm of cloud computing with a focus on how it offers a customized and tailor-made approach to address the challenges of scalability and operational efficiency. This comparative study examines how private cloud infrastructures empower organizations to adjust their resources based on their requirements. In this paper, we will explore private cloud solutions in-depth, focusing on their ability to meet specific business needs, foster growth, and improve operational efficiency. Beyond the basics, we will also address the challenges faced by businesses in implementing private cloud infrastructures. Through rigorous analysis, real-world case studies, and industry best practices, we identify these challenges and offer innovative strategies to overcome them. In this study, we will also explore load-balancing techniques analyzing strategies for resource optimization and system performance enhancement. While private clouds offer many benefits, organizations need to assess their specific requirements and weigh these advantages against the potential limitations, such as higher initial setup costs and the urgency for in-house expertise for management and maintenance. Many businesses also opt for hybrid cloud solutions, combining elements of both private and public clouds to achieve a balance between control, flexibility, and scalability. Our purpose centers on the throttled load balancing algorithm, an innovative method for efficient network load management.